Aiaa Aviation 2020 Forum 2020
DOI: 10.2514/6.2020-2900
|View full text |Cite
|
Sign up to set email alerts
|

A Risk-based UAS Traffic Network Model for Adaptive Urban Airspace Management

Abstract: This paper presents a risk-based model for UAV path planning in urban low altitude environments. Firstly, the risks in urban environments were identified and classified into four groups, and the corresponding risk costs were categorized into five different levels. A general risk cost model was then developed for qualifying all related risk costs. Secondly, a ConOps for urban air route network with plane and cubical diagonals was built and the obtained risk cost information were ingested into the network to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…Having demonstrated that there is a potential demand for flying taxis in Singapore, particularly in tourist areas, and how users can benefit from it, there is an urgent need to create the infrastructure and systems necessary for the use of UAM safely in Singapore. Future research can concentrate more on airworthiness, risk analysis [18], airspace management [19] in the short-term, Detect and Avoid (DAA), ground infrastructure, community acceptance in the mid-term and cybersecurity in the long-term. As the present study focuses mainly on fares and times spent for the trips, other factors should be considered, like the phases of the flying path, suitable sites of take-off and landing, technology and safety requirements for the whole operation including pre-, post-, and cruising of the drone's flying.…”
Section: Discussionmentioning
confidence: 99%
“…Having demonstrated that there is a potential demand for flying taxis in Singapore, particularly in tourist areas, and how users can benefit from it, there is an urgent need to create the infrastructure and systems necessary for the use of UAM safely in Singapore. Future research can concentrate more on airworthiness, risk analysis [18], airspace management [19] in the short-term, Detect and Avoid (DAA), ground infrastructure, community acceptance in the mid-term and cybersecurity in the long-term. As the present study focuses mainly on fares and times spent for the trips, other factors should be considered, like the phases of the flying path, suitable sites of take-off and landing, technology and safety requirements for the whole operation including pre-, post-, and cruising of the drone's flying.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, the third-party risk [41] (i.e. ground people, manned aircraft) can also be mitigated because the high LoA is assumed to have abilities to avoid high risk areas by conducting risk-based path planning [42], [43], and by performing conflict resolutions with manned and other unmanned aircraft with advanced DAA capabilities [44]. UAS with higher LoA would also help improve the efficiency of the UTM network.…”
Section: A Overview Of Loamentioning
confidence: 99%
“…In [Figure 9Figure 6], the first drone was malfunction when it is flying to target location. And then, the first drone pilot reported to the UTM system as 10 meters diameter risk zone [21]. The UTM system received and confirm the temporary risk zone of drone #1 and sent the temporary risk zone info to drone #2 and #3 and to hold their position.…”
Section: Ntu Campus Utm Architecturementioning
confidence: 99%